What Makes Consumers Impulsive During Online Shopping: Hedonic Vs. Utilitarian Browsing? - Akter, Mansura; Niloy, Md. Abdur Rahman (Bangladesh Journal of MIS, 2025)
The rapid expansion of e-commerce in Bangladesh has ushered in a new era of consumer behavior, particularly in impulse purchases made while shopping online. This study explores the impact of hedonic (pleasure-driven) and utilitarian (goal-oriented) browsing on online impulse buying behavior in Bangladesh’s rapidly growing e-commerce sector. Using an online survey and binary logistic regression analysis, the research reveals that both browsing types contribute to impulse purchases, but hedonic browsing has a stronger influence—68% of respondents reported making impulse buys during such sessions. Gender plays a significant role: 94% of female participants engaged in impulse buying during hedonic browsing, while 69% of males did so during utilitarian browsing. Key factors positively influencing impulse buying include gender, attractive product displays, peer recommendations, credit card availability, and promotional activities. Interestingly, discount offers were found to negatively affect impulse buying. Product preferences also vary by gender—females tend to impulsively buy clothes, apparel, and cosmetics, whereas males are more likely to purchase electronics and gadgets. The study contributes to consumer behavior theory by highlighting the dual influence of browsing types on impulse buying. Practically, it offers insights for e-commerce platforms to design gender-targeted marketing strategies and personalized offers, leveraging social influence and financial tools to boost sales and customer satisfaction. These findings are particularly relevant for businesses aiming to optimize their digital marketing efforts in Bangladesh’s evolving online retail landscape.